2023
DOI: 10.1007/s10935-023-00737-z
|View full text |Cite
|
Sign up to set email alerts
|

How Specific is Alcohol-Specific Self-Control? A Longitudinal Study of the Mediating Role of Alcohol-Specific Self-Control in the Relation Between General Self-Control and Adolescent Alcohol Use

Abstract: Although accumulating studies indicate that alcohol-specific self-control can be useful in predicting adolescent alcohol use, little is known about its specificity. This longitudinal study aimed to advance our understanding of domain-specific self-control by examining whether alcohol-specific self-control mediates the effect of general self-control on adolescent alcohol use or has generalizing effects by also mediating the effect of general self-control on other behavior requiring self-control (adolescent digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Previous cross-sectional studies have found that exposure to short-form video and social media involvement have increased individuals’ motivation to overcome alcohol consumption ( Russell et al, 2021 ; Zeping, 2023 ). In addition, scholars have extensively examined key determinants such as attitudes toward alcohol ( Morgenstern et al, 2011 ), self-control ( Geurts et al, 2020 ), and perceived risk ( Wolburg, 2001 ) that contribute to individuals’ willingness to reduce alcohol consumption (WRAC) across countries. The majority of studies have examined both direct and mediated effects of factors on WRAC under social psychological and cognitive theories (e.g., theory of planned behavior, theories of motivation, and social cognition) ( Caudwell et al, 2019 ; Ajzen and Schmidt, 2020 ; Hagger and Hamilton, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous cross-sectional studies have found that exposure to short-form video and social media involvement have increased individuals’ motivation to overcome alcohol consumption ( Russell et al, 2021 ; Zeping, 2023 ). In addition, scholars have extensively examined key determinants such as attitudes toward alcohol ( Morgenstern et al, 2011 ), self-control ( Geurts et al, 2020 ), and perceived risk ( Wolburg, 2001 ) that contribute to individuals’ willingness to reduce alcohol consumption (WRAC) across countries. The majority of studies have examined both direct and mediated effects of factors on WRAC under social psychological and cognitive theories (e.g., theory of planned behavior, theories of motivation, and social cognition) ( Caudwell et al, 2019 ; Ajzen and Schmidt, 2020 ; Hagger and Hamilton, 2021 ).…”
Section: Introductionmentioning
confidence: 99%